Analisis Perbandingan Kualitas Jaringan 4G LTE Operator X Dan Y Di Wilayah Kampus Utama UMSU - Evalina, Noorly (P3M Politeknik Negeri Medan, 2021)
A technology appears, namely Long Term Evolution (LTE), which is a fourth generation (4G) cellular network technology. This LTE can provide data transfer speeds of up to 100 Mbps on the downlink side and 50 Mbps on the uplink side. The growth in the number of telecommunication service users in Medan City has caused a decline in network quality, especially 4G LTE technology. By doing a drive test, it can be seen the areas where there is signal strength of a network which aims to improve the signal quality of a network. Benchmark (comparison) of 4G LTE operator service quality is done by measuring, comparing, and analyzing the network quality (performance) of two 4G LTE operators around the Muhammadiyah University of North Sumatra campus. The overall throughput value of operator X is only 0> 3 Mbps, while operator Y is 0> 30 Mbps. The very low throughput value is caused by high traffic users during the day, where the Muhammadiyah University of North Sumatra campus is actively studying and many students use data services. That way, people can find out the causes of the internet speed problems they feel when using the internet during the day.